A minireview on the synthesis of single atom catalysts. Issue 15 (24th March 2022) - Guo, Jiawen; Liu, Huimin; Li, Dezheng; Wang, Jian; Djitcheu, Xavier; He, Dehua; Zhang, Qijian
Abstract : The two routes for the synthesis of SACs are reviewed and the advantages and disadvantages of each method are compared. Abstract : Single atom catalysis is a prosperous and rapidly growing research field, owing to the remarkable advantages of single atom catalysts (SACs), such as maximized atom utilization efficiency, tailorable catalytic activities as well as supremely high catalytic selectivity. Synthesis approaches play crucial roles in determining the properties and performance of SACs. Over the past few years, versatile methods have been adopted to synthesize SACs. Herein, we give a thorough and up-to-date review on the progress of approaches for the synthesis of SACs, outline the general principles and list the advantages and disadvantages of each synthesis approach, with the aim to give the readers a clear picture and inspire more studies to exploit novel approaches to synthesize SACs effectively.